1975
DOI: 10.1161/01.str.6.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Chronically Impaired Autoregulation of Cerebral Blood Flow in Long-Term Diabetics

Abstract: Abstract:Chronically Impaired Autoregulation of Cerebral Blood Flow in Long-Term Diabetics • Using the arteriovenous oxygen difference method autoregulation of cerebral blood flow (CBF) was tested in 16 long-term diabetics and eight control patients. Blood pressure was raised by angiotensin infusion and lowered by trimethaphan camsylate infusion, in some cases combined with head-up tilting of the patient. Regression analysis was carried out on the results in order to quantify autoregulatory capacity.In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
48
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 23 publications
9
48
0
1
Order By: Relevance
“…In diabetic subjects cerebral blood flow is less rigidly controlled than in normal subjects, suggesting impaired autoregulation [12,13]. Apart from this no information is available on autoregulation in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetic subjects cerebral blood flow is less rigidly controlled than in normal subjects, suggesting impaired autoregulation [12,13]. Apart from this no information is available on autoregulation in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Arteriolar tone is influenced by local changes in concentrations of various metabolites including adenosine [7], pyrophosphate [8] and potassium [9]. Furthermore, local changes in oxygen [10] and carbon dioxide tensions [11] may play an important role.In diabetic subjects cerebral blood flow is less rigidly controlled than in normal subjects, suggesting impaired autoregulation [12,13]. Apart from this no information is available on autoregulation in diabetes.…”
mentioning
confidence: 99%
“…Early diabetes mellitus in both experimental animals and man is associated with increased blood flow to many tissues, including the kidney, myocardium, retina, skin, muscle, and brain (1)(2)(3)(4)(5)(6)(7). These early changes in regional hemodynamics have in turn been strongly implicated in the pathogenesis of the widespread microvascular injury that characterizes this disease (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the autoregulatory disturbances in our patients were relatively subtle. Previous studies have also reported relatively mild alterations in cerebral blood flow autoregulation in patients with diabetes [16,17]. In some diabetic patients, impaired autoregulation might contribute to orthostatic hypotension [9], which is a known risk factor for ischaemic stroke [18].…”
Section: Discussionmentioning
confidence: 95%